Effect of co-inoculation with plant growth-promoting bacteria on the microbiome of soybean roots - de Andrade da Silva, Maura Santos Reis [UNESP]; de Carvalho, Lucas Amoroso Lopes [UNESP]; Santos, Carlos Henrique Barbosa [UNESP]; Frezarin, Edvan Teciano [UNESP]; da Silva, Cleudison Gabriel Nascimento; Pinheiro, Daniel Guariz [UNESP]; Zonta, Everaldo; Babalola, Olubukola Oluranti; Rigobelo, Everlon Cid [UNESP] (Frontiers, 2025)
Introduction: The effect of co-inoculation with plant growth-promoting bacteria on the microbiome of soybean roots was investigated in a field experiment. Soybean plants were inoculated with Bacillus subtilis, Bacillus aryabhattai, Streptomyces sp., and Saccharopolyspora spinosa and compared to a control treatment that received mineral fertilization. Methods: The yield parameters and endophytic microbiome of soybean roots were evaluated. Results: No significant differences in yield were observed among the treatments, suggesting that microbial inoculation can serve as an alternative to mineral fertilization without compromising productivity. Among the most abundant genera, there was a high prevalence of members of the phylum Proteobacteria (21 of the top 25 genera). Overall, the genera of these phyla represented 88.61% of the samples on average. There were also genera in the phyla Bacteroidetes (2/25), Actinobacteria (1/25), and Firmicutes (1/25). The massive presence of Bradyrhizobium, which represented 71.22% of the sequences at the genus level, was remarkable. Bradyrhizobium was the most abundant genus in all samples, except for Saccharopolyspora spinosa (ST treatment), whose abundance was only 12.66%. Co-occurrence network analysis revealed changes in the microbial community structure and genera considered as hubs. Discussion: These findings demonstrate the potential of co-inoculation with plant growth-promoting bacteria to modulate the root microbiome and enhance the colonization of B. japonicum, which may contribute to improving the efficiency of this symbiont in promoting plant growth. Further research is required to elucidate the mechanisms underlying these interactions and their implications for soybean productivity.
Keywords: metagenomic; microbiome; plant growth; Saccharopolyspora spinosa; Streptomyces